1997
DOI: 10.1192/apt.3.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of relapse and recurrence of depression: newer versus older antidepressants

Abstract: In a 17- to 19-year follow-up study it was shown that patients admitted to the Maudsley Hospital, London (whose index episode marked their first psychiatric contact) had a 50% chance of readmission during their lifetime; those with previous admissions had a similar chance of readmission within three years. Less than one-fifth of the patients had remained well, and over one-third suffered severe chronic distress and handicap or had died unnaturally (Lee & Murray, 1988). Similar gloomy pictures were reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In recent years there has been a significant increase in the use of the SSRIs as first-line treatment for depression, replacing the older antidepressants, principally the tricyclics (Amytriptyline, Imipramine). The predicted cost for such a change in terms of national prescribing in England is in the order of s million (Edwards 1997). One would expect that such a massive increase in expenditure would be supported by convincing empirical evidence demonstrated by the gold standard of RCT evidence.…”
Section: Antidepressant Treatment As a Paradigmmentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years there has been a significant increase in the use of the SSRIs as first-line treatment for depression, replacing the older antidepressants, principally the tricyclics (Amytriptyline, Imipramine). The predicted cost for such a change in terms of national prescribing in England is in the order of s million (Edwards 1997). One would expect that such a massive increase in expenditure would be supported by convincing empirical evidence demonstrated by the gold standard of RCT evidence.…”
Section: Antidepressant Treatment As a Paradigmmentioning
confidence: 95%
“…Hotopf et al (1997a) concluded that SSRIs have some advantage over older tricyclics, which do have more extensive side effects, but no significant difference was found when compared to newer tricyclics or hertrocyclics. It is acknowledged that death due to overdose is more likely to occur if older antidepressants (TCAs) are taken, however only 4% of all completed suicides are due to overdose of a single antidepressants (Edwards 1997). Furthermore, tricyclics tend to be prescribed for patients with severe depression/in-patients who are often considered to be the patients who are at increased risk of suicide.…”
Section: Antidepressant Treatment As a Paradigmmentioning
confidence: 99%
“…The January 1997 issue of this journal contained four reviews that compared tricyclic antidepressants with selective serotonin reuptake inhibitors (SSRIs) and other newer antidepressants in terms of their pharmacology (Palazidou, 1997), adverse effects, potential drug interactions and toxicity (Henry, 1997), efficacy in the prevention of relapse and recurrence (Edwards, 1997), and findings from metaanalyses (Anderson, 1997). In July 1997 reboxetine was promoted as the first selective noradrenaline reuptake inhibitor (NARI), and in October of the same year mirtazapine was promoted as the first noradrenergic and specific serotonergic antidepressant (NaSSA).…”
Section: Unresolved Controversies About Newer Antidepressants Snrismentioning
confidence: 99%
“…There is still no clear consensus as to first line treatment in the elderly [4] and the debate continues in the professional literature. Advocates of tricyclic antidepressants (TCAs) as first line treatment concentrate their arguments on their known efficacy in moderate to severe depression and their apparent cost‐effectiveness, arguing that new products such as selective serotonin re‐uptake inhibitors (SSRIs) should be reserved for those patients who cannot tolerate the side‐effects of tricyclics antidepressants [5]. This argument is reinforced by the claim that the SSRIs as a class may be less effective in the treatment of severe depression, although this is based on relatively little evidence.…”
Section: Introductionmentioning
confidence: 99%